2020
DOI: 10.1002/cbin.11445
|View full text |Cite
|
Sign up to set email alerts
|

High‐glucose concentration aggravates TNF‐alpha‐induced cell viability reduction in human CD146‐positive periodontal ligament cells via TNFR‐1 gene demethylation

Abstract: Periodontitis is a chronic inflammatory disease that results in the destruction of periodontal soft tissue and the resorption of alveolar bone. Evidence indicates that in diabetic patients, hyperglycemia suppresses periodontal ligament stem cell (PDLSC) functions and leads to difficulties in periodontal repair. The present study aimed to explore the mechanisms by which high‐glucose concentrations aggravate cell viability reduction in human CD146‐positive PDLCs (CD146+PDLCs) under tumor necrosis factor‐alpha (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…In the present study, miR-29c-3p was found to be targeted and regulated by circSAMD4A. Although miR-29c-3p has been reported to participate in the pathogenesis of multiple human diseases, such as colorectal cancer, ovarian cancer and AD (48)(49)(50), to the best of our knowledge, its role in PD has not been previously reported. In the current study, miR-29c-3p was identified to abolish the protective effects of circSAMD4A knockdown against MPTP-or MPP + -induced apoptosis and autophagy.…”
Section: Discussionmentioning
confidence: 41%
“…In the present study, miR-29c-3p was found to be targeted and regulated by circSAMD4A. Although miR-29c-3p has been reported to participate in the pathogenesis of multiple human diseases, such as colorectal cancer, ovarian cancer and AD (48)(49)(50), to the best of our knowledge, its role in PD has not been previously reported. In the current study, miR-29c-3p was identified to abolish the protective effects of circSAMD4A knockdown against MPTP-or MPP + -induced apoptosis and autophagy.…”
Section: Discussionmentioning
confidence: 41%
“…Here, we selected TNF-α to mock the microenvironment of periodontitis, and we established a TNF-α concentration gradient to explore biological behaviors of inflammatory PDLSCs. Coherent with existed literatures [41,45,46], TNF-α inhibited cell viability and increased expression of inflammatory genes via the NF-κB signaling pathway. Fang et al [47] and Meng et al [41] mentioned that TNF-α could also induce apoptosis and oxidative stress of PDLSCs, which was analogous to our study.…”
Section: Discussionmentioning
confidence: 79%
“…Several studies showed that PDL cells expressed TNFRs [ 38 , 39 , 40 , 41 ]. Furthermore, it has been reported that the expression levels of TNFRs in CD146 positive PDL cells were higher than those in CD146 negative PDL cells, and TNF-α was found to have higher level of biological effect in CD146 positive PDL cells than in CD146 negative PDL cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%